Protective Immunity Elicited by Oral Immunization of Mice with Salmonella enterica Serovar Typhimurium Braun Lipoprotein (Lpp) and Acetyltransferase (MsbB) Mutants - Erova, Tatiana E.; Kirtley, Michelle L.; Fitts, Eric C.; Ponnusamy, Duraisamy; Baze, Wallace B.; Andersson, Jourdan A.; Cong, Yingzi; Tiner, Bethany L.; Sha, Jian; Chopra, Ashok K. (Frontiers in Cellular and Infection Microbiology, 2016)
We evaluated the extent of attenuation and immunogenicity of the ∆lppAB and ∆lppAB ∆msbB mutants of Salmonella enterica serovar Typhimurium when delivered to mice by the oral route. These mutants were deleted either for the Braun lipoprotein genes (lppA and lppB) or in combination with the msbB gene, which encodes an acetyltransferase required for lipid A modification of lipopolysaccharide. Both the mutants were attenuated (100% animal survival) and triggered robust innate and adaptive immune responses. Comparable levels of IgG and its isotypes were produced in mice infected with wild-type (WT) S. Typhimurium or its aforementioned mutant strains. The ∆lppAB ∆msbB mutant-immunized animals resulted in the production of higher levels of fecal IgA and serum cytokines during later stages of vaccination (adaptive response). A significant production of interleukin-6 from T-cells was also noted in the ∆lppAB ∆msbB mutant-immunized mice when compared to that of the ∆lppAB mutant. On the other hand, IL-17A production was significantly more in the serum of ∆lppAB mutant-immunized mice (innate response) with a stronger splenic T-cell proliferative and tumor-necrosis factor-α production. Based on 2-dimensional gel analysis, alterations in the levels of several proteins were observed in both the mutant strains when compared to that in WT S. Typhimurium and could be associated with the higher immunogenicity of the mutants. Finally, both ∆lppAB and ∆lppAB ∆msbB mutants provided complete protection to immunized mice against a lethal oral challenge dose of WT S. Typhimurium. Thus, these mutants may serve as excellent vaccine candidates and also provide a platform for delivering heterologous antigens.